POTRET PENDIDIKAN DI INDONESIA DAN KESIAPANNYA DALAM MENGHADAPI MASYARAKAT EKONOMI ASIA (MEA) - Heri Widodo (Cendekia: Kependidikan dan Kemasyarakatan, 2015)
Abstracts: Education determines the progress of a nation to be a prosperous country. With education, the pride and civilization of a nation is easily realized. This paper is a small portrait of educational system and educational quality in Indonesia; quality of education is directly correlated to the quality of the graduated in Indonesia. Human resources in Indonesia are deeply affected by quality of education in Indonesia. The fact found that only the qualified human resources can be absorbed in work places. In line with the global live, Indonesians are parts of Asia community and world community, therefore, Indonesians are required to move on following requirement of world community. To cope the existence of “MEA”changes on education paradigm and making wisdom decisions must be done appropriately that Indonesians can be actively involved in “MEA” and they are not merely the objects of other Asia Countries.  ةيناكما ةدّ يلجا ةيبترلابو .ايندم اعمتمج هنوك لىإ لوصولل بعشلا رّ وطتو ّ ونم ينيعت في اسايقم ةيبترلا تناك ماظن نع ةيرغص ةروص ضرع ةلاقلما هذه تلواح .ةمّ دقتم ةراضح اذ ايمرك ابعش بعشلا نوك تاينمأ ققتح ينجّ رلخا ةدوجو ،ينيجّ رلخا ةدوج ىوتسم ىلع ةرشابم رثؤت ةيبترلا ةدوج نلأ ،ايسينودنإ في اهتدوجو ةيبترلا .لمعلا نيدايم اهيلإ جاتتح تيلا يه ةدّ يلجا ةيناسنلإا دراولماو .ايسينودنإ ىدل ةيناسنلإا دراولما ةيعون في رّ ثؤت اذهب .لماعلا في تاعمتلمجا نم ضعبو ،ايسآ عمتمج نم ضعب ايسينودنإ نإف ةلموعلا رصع في ةايلحا بناج فيو يداصتقلإا عمتلمجا دوجوبف .رصاعلما يلماعلا عمتلمجا تايضتقم ةرياسم  ّ يسينودنلإا بعشلا وطيخ نأ دبلا نم دبلا ةمكلحاب رصعلا تايضتقلم فقولما ذاتخاو ةيبترلا في رظنلا تاهجو تايريغت  ّ نإف   يويسلآا قاوسلأا نم اقوس ايسينودنإ نوكت لا نلأو   في كاترشلاا ىلع يسينودنلإا بعشلا ردقيل اهب مايقلا .لودلا نم اهيرغل